Real-Time Infrared Thermography at ASDEX Upgrade. (1st May 2016) - Sieglin, B; Faitsch, M; Herrmann, A; Martinov, S; Eich, T; Team, ASDEX Upgrad
Abstract: Infrared (IR) thermography is a widely used tool in fusion research to study the thermal load onto plasma-facing components. In present-day fusion experiments with short-pulse duration, off-line data analysis is still feasible. For devices with long-pulse duration and actively cooled plasma-facing components, IR thermography is a common tool for machine protection. In future fusion devices with long-pulse duration, online data evaluation of the thermography measurement for additional physics studies is required. Real-time–capable IR thermography was developed at ASDEX Upgrade. The feasibility of real-time thermography is discussed in this work. The evaluation process from raw data to evaluated temperature and heat flux is shown. The real-time version of the THEODOR code allows online calculation of the heat flux. Exploiting the possibility of the IR system to change the integration time during acquisition opens up the possibility to have automated thermography. The current status of the thermography system at ASDEX Upgrade and future developments for its improvement are discussed.